2004
DOI: 10.1074/jbc.m401267200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Calpain Cleavage of Huntingtin Reduces Toxicity

Abstract: Huntington's disease (HD) is a neurodegenerative disorder caused by a polyglutamine (polyQ) tract expansion near the N terminus of huntingtin (Htt). Proteolytic processing of mutant Htt and abnormal calcium signaling may play a critical role in disease progression and pathogenesis. Recent work indicates that calpains may participate in the increased and/or altered patterns of Htt proteolysis leading to the selective toxicity observed in HD striatum. Here, we identify two calpain cleavage sites in Htt and show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 244 publications
(94 citation statements)
references
References 60 publications
(67 reference statements)
3
91
0
Order By: Relevance
“…Procaspase-7 is localized to both the cytosolic and nuclear compartment suggesting activation can occur in either compartment. This is consistent with the localization of caspases and calpains to both subcellular locations (19). It follows that calpain cleavage of caspase-7 can occur in either compartment.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Procaspase-7 is localized to both the cytosolic and nuclear compartment suggesting activation can occur in either compartment. This is consistent with the localization of caspases and calpains to both subcellular locations (19). It follows that calpain cleavage of caspase-7 can occur in either compartment.…”
Section: Discussionsupporting
confidence: 72%
“…We and others (17,19) have previously shown that mutating a single amino acid is not adequate to prevent recognition of the substrate. Therefore we used deletion analysis in which we removed three amino acids in the region of cleavage.…”
Section: Confirmation Of the Three Calpain Cleavage Sites In Caspase-mentioning
confidence: 99%
“…Caspase enzymes that can cleave Htt include caspase-2, -3, -6, and -7, and cleavage occurs between amino acids 513 and 587 (9,11,12). Htt is cleaved in several places by calpains as well (13,14) and this may also contribute to toxicity (15). The major calpain sites are located between amino acids 469 and 537 (13,15).…”
Section: Huntington Disease (Hd)mentioning
confidence: 99%
“…Htt is cleaved in several places by calpains as well (13,14) and this may also contribute to toxicity (15). The major calpain sites are located between amino acids 469 and 537 (13,15).…”
Section: Huntington Disease (Hd)mentioning
confidence: 99%
“…The proteases of this family have been implicated previously in Htt proteolysis; calpain-mediated cleavage of Htt (at residues 469 and 536) may be linked to mutant Htt toxicity (10,(21)(22)(23)25). Our previous findings indicate that calpain may be also involved in degradation of cp-1/cp-2 fragments as calpain inhibitors caused increased fragment accumulation in PC12 cells (32).…”
Section: Discussionmentioning
confidence: 97%